Steady-state scratch testing of polymers - Blackman,BRK; Hoult,T; Patel,Y; Steininger,H; Williams,JG (Polymer Testing, 2015)
The paper extends the notion of steady-state cutting of polymers with a sharp tool to scratching. The analysis assumes there is separation at the tool tip (fracture) and the removed layer undergoes plastic shear. Results are presented for three polymers: PMMA, PC and PBT. For the tougher polymer, PC, smooth scratches were obtained and the modified cutting analysis works well provided that the wear on the initially sharp tip is accounted for. For the more brittle polymers, PMMA and PBT, rougher scratches were obtained and this is consistent with the notion that the polymers exhibited micro-cracking ahead of the tool tip, which led to rough surfaces being generated. The results demonstrate that the fracture toughness and the yield stress are controlling parameters in the scratching process and that a sufficiently high value of crack opening displacement COD (greater than about 10 μm) ensures that smooth scratches are obtained, as was the case for PC.